Scaffolding Writing Model Based on Diary to Improve Moral Intelligence for Elementary School Students - Ayuningtyas, Riva; Supriatna, Nana (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This study aims to improve 21st century life skills in elementary school students based on morals. One way that can be done to achieve this is by instilling and providing moral intelligence from an early age in accordance with the core competencies of KI - 2, namely the social aspects contained in basic competence 2.3 in social studies subjects grade V in elementary schools, namely being tolerant in diversity. religious people in society in the context of Bhinneka Tunggal Ika. The process of inculcating moral intelligence is carried out through a creative writing model based on a diary. The diary-based creative writing model is a multiliterate learning that encourages students to analyze moral issues based on their respective student activities. This model consists of the following stages. (1) pre-write; (2) write; and (3) post writing. This study uses a quantitative approach with a pre-experimental method of non-equivalent pretest posttest design. The results of this study indicate that the application of a diary-based creative writing model is able to increase students' knowledge of moral intelligence by 1.08 (the difference between pretest and posttest results) with the quality of improvement in the medium category. The increase in students' moral intelligence can be seen when students write down identification results in diaries related to moral intelligence, give reasons for activities that have been classified as good and bad, and make plans for activities to be carried out as preventive and countermeasures based on their diaries.